Mekanisme Mekanisme Pengangkatan Penjabat Kepala Daerah Perspektif Imam al-Mawardi (Studi Permendagri No 4 Tahun 2023) - Muhammad Ilham Tahir; Asri Asri; Irsyad Rafi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
The purpose of this study is to analyze Imam al-Mawardi's perspective on the concept of the appointment mechanism for regional heads based on the Minister of Home Affairs Regulation Number 4 of 2023. This research is a library research using a juridical-normative approach. The results of this study indicate that the mechanism for appointing regional heads is regulated in the Minister of Home Affairs Regulation Number 4 of 2023 as a follow-up to the Constitutional Court Decision Number 15/PUU-XX/2022, which states that the President, as the highest leader, decides the acting governors after proposing six candidates, and the Minister of Home Affairs decides the acting regents and mayors after proposing nine candidates. The appointment of these regional heads aims to fill 271 vacant regional head positions due to the postponement of regional elections. According to al-Mawardi, the appointment of regional heads is carried out by the caliph and can also be done by the wazir tafwidī as the caliph's representative. The results of this study show that the concept of the appointment mechanism for regional heads carried out by the President and the Minister of Home Affairs is in line with Imam al-Mawardi's perspective. However, the appointment of regional heads due to special conditions caused by the postponement of regional elections contradicts Imam al-Mawardi's perspective, as the appointment of regional heads is the duty of a caliph and the wazir tafwidī, not by the entire population. The contribution of this study provides insights into the mechanism for appointing regional heads from Imam al-Mawardi's perspective and serves as a reference for the government to consider the concept of direct appointment of regional heads, as the direct election system is prone to causing conflicts within the community